The influence of e-customer service quality and extrinsic brand attributes on brand evangelism among top five Malaysian telecommunication brands: the moderating role of interactive services and the mediating role of brand preference and repurchase intention / Mohamad Atheef Hannan M. Suaree - M. Suaree, Mohamad Atheef Hannan (2023)
Brand evangelism is a new strategy for Malaysian telecommunication brand turn consumers into brand evangelists who passionately embrace their favourite brands by enthusiastically sharing their positive brand experiences with others, encouraging others to experience the brand, and discouraging others from purchasing competing brands. This marketing strategy signifies more proactive and devoted referrals behaviour and more aggressive persuasion of others to consume the same brand. Based on the behavioral decision theory, this study investigates the impact of e-customer service execution on consumer decision journey with the dimension of e-customer service quality and extrinsic brand attributes towards positive brand referrals as well as oppositional brand referrals with the moderating role of interactive services and the mediating role of brand preference and repurchase intention.